Cu+ ions extraction of the modified Bernas ion source - Trịnh, Thị Tú Anh (2023)
Gas ion implanter using Duopigatron ion sources has been used to improve surface properties of the material at PEFP(Proton Engineering Frontier Project). Gas ion implanter is limited to ion species such as feeding gases. Bernas ion source with heating elements is adopted to use heavy ions like metals. This paper is presented about feasibility of the Cu+ ions extraction from the ion source